Cardiac Arrhythmias in Ischemic Stroke Patients Admitted in a Tertiary Medical College of Central Nepal - Nepal, Bikash; Mishra, Rajeev; Verma, Avatar; Chapagain, Prativa; Chapagain, Prabin; Dewan, Khush Raj; Mishra, Ganapati; Rana, PVS (Journal of National Heart and Lung Society Nepal, 2023)
Background: Cardiac arrhythmias are known etiological agent for ischemic stroke and are also common after acute ischemic stroke. The objective of this research is to study various cardiac arrhythmias and find incidence of atrial fibrillation in acute ischemic stroke. Methods: This hospital based cross sectional study conducted at COMS - teaching Hospital included 100 patients with diagnosis of acute ischemic stroke from October 2015 to October 2016. Arrhythmias was classified as atrial ectopic beats, atrial fibrillation, premature ventricular complex, sinus bradycardia, sinus tachycardia, sinus arrhythmias, sick sinus syndrome, atrial tachycardia and ventricular tachycardia on basis of ECG monitoring for 24 hours. Results: Among total 56% (n=56) had abnormal rhythm. Total incidence of atrial fibrillation was 20%. Other arrhythmias observed were sinus tachycardia in 9% (n=9), premature ventricular complex in 8% (n=8), ventricular tachycardia in 5% (n=5), sinus bradycardia in 4% (n=4), sinus arrhythmias in 4% (n=4), atrial ectopic beats in 3% (n=3), sick sinus syndrome in 2% (n=2) and atrial tachycardia in 1%(n=1). Right cerebral hemisphere was more involved than left in both normal and abnormal rhythm (p =0.714). Mortality observed was 4.5% (n=2) in normal rhythm and 8.9% (n=5) in arryhthmias (p=0.461). Conclusion: Cardiac arrhythmias are frequent in acute ischemic stroke. Atrial fibrillation is most commonly observed arrhythmia in acute ischemic stroke and mortality is higher in patient with rhythm abnormalities than with normal rhythm.